2015
DOI: 10.1038/ni.3120
|View full text |Cite
|
Sign up to set email alerts
|

NK cells link obesity-induced adipose stress to inflammation and insulin resistance

Abstract: An important cause of obesity-induced insulin resistance is chronic systemic inflammation originating in visceral adipose tissue (VAT). VAT inflammation is associated with the accumulation of proinflammatory macrophages in adipose tissue, but the immunological signals that trigger their accumulation remain unknown. We found that a phenotypically distinct population of tissue-resident natural killer (NK) cells represented a crucial link between obesity-induced adipose stress and VAT inflammation. Obesity drove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
450
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(488 citation statements)
references
References 54 publications
29
450
3
6
Order By: Relevance
“…Using the Ncr1 gfp/gfp mice, it was revealed that Ncr1 is involved in controlling influenza virus infections (5,22,25), tumor and metastases eradication (6,7,10,24), the development of type I and type II diabetes (11,23,26,27), liver fibrosis (28), and bacterial infections (3,29). In all of these studies, the activity of the Ncr1 gfp/gfp NK cells was impaired in an Ncr1-dependent manner.…”
mentioning
confidence: 99%
“…Using the Ncr1 gfp/gfp mice, it was revealed that Ncr1 is involved in controlling influenza virus infections (5,22,25), tumor and metastases eradication (6,7,10,24), the development of type I and type II diabetes (11,23,26,27), liver fibrosis (28), and bacterial infections (3,29). In all of these studies, the activity of the Ncr1 gfp/gfp NK cells was impaired in an Ncr1-dependent manner.…”
mentioning
confidence: 99%
“…Studies using rodent models show that obesity-related stress alters immune cell polarization in metabolically active organs such as adipose tissue, pancreas, and liver (9)(10)(11). For example, recent work has highlighted the importance of immunomodulatory factors (i.e., type-2 cytokines) produced by immune cells for maintaining healthy metabolic homeostasis in adipocytes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…tumor cells, NK cells can respond to allogeneic, virus-infected, and stressed cells (13,14). NK cells are early potent producers of IFN-γ, a cytokine that plays a key role in tumor immunosurveillance and activates the inflammatory cascade against neoplastic threat (15).…”
Section: Introductionmentioning
confidence: 99%